Intergenerational mobility: Measurement and the role of borrowing constraints and inherited tastes - Jordi Caballé (SERIEs - Journal of the Spanish Economic Association, 2016)
In this paper, I present some popular measures of mobility in economic outcomes within a family across generations. I also discuss two of the most important factors preventing intergenerational mobility: existence of financially constrained individuals and transmission of tastes from parents to children. Finally, I show how these two factors could give raise to dramatic reversals of fortune affecting successive generations of the same dynasty. I will cast the results of the different models I use in terms of the previous measures of intergenerational mobility.
Keywords: J62; E21; I26; 330; Intergenerational mobility; Inherited tastes; Borrowing constraints